Lock your windows. - Burns, Simon (Far Eastern Economic Review, 2000)
The writer discusses two easy-to-use security software packages to protect homes and small businesses against hackers. He argues that BlackIce Defender, a program from software developer Network Ice, and ZoneAlarm, produced by Zone labs, both work to defend your computer from intruders by constantly monitoring the PC's Internet connection for suspicious activity. He outlines how this software functions, considers why hackers would be interested in breaking into an ordinary home computer, and evaluates the products' performances.